Non-Communicable Disease (NCD) Health Efforts in the Productive Age at the Community Health Center - Alya Nurul Husna, Qurratul Ain; Angela Ramanda Putri; Dhita Ayu Kinantari Dewie; Nur Isnaeni Evry Kurniawati (Jurnal Kesehatan dan Kedokteran, 2025)
Introduction: Non-communicable diseases (NCDs) such as heart disease, cancer, diabetes, and respiratory diseases are the leading causes of global deaths, accounting for about 74% of total deaths. Hypertension and diabetes are the main diseases and risk factors for NCDs. Results: SKI 2023 stated that the prevalence of NCDs at the highest productive age was occupied by hypertension and diabetes. As many as 53.5% of disabilities are caused by NCDs. In order to overcome, the government implements the Minimum Health Service Standards (SPMK) in accordance with the Type of Basic Service and Quality of Basic Services. In its implementation, a Primary Service Integration system was prepared whose approach is lifecycle-based and community-based to make it easier to implement. Method: This article was compiled using a literature study method with a descriptive approach.Conclusion: The need to optimize health centers in all services and the need for the role of cross-sector cooperation and collaboration, including community empowerment in maximizing service efforts.